Ab-initio DFT modeling of the oxidation of methane on transition metal catalysts - Psofogiannakis, George (University of Ottawa (Canada), 2007)
Quantum-mechanical Density Functional Theory (DFT) calculations were performed in order to study catalytic aspects of the oxidation of methane on transition metal catalysts. Metal clusters were used to model the metal surfaces. The work is related to two different systems: the first is the direct electrocatalytic oxidation of methane in fuel cells to produce electrical power. The second is the steam-reforming of methane to produce synthesis gas. Both processes involve the adsorption, dissociation and transformation of methane and water on the surface of a metal catalyst. The work was divided into three parts. In the first part, the mechanism of electrooxidation of methane on a Pt(111) surface was studied. The activation energies of surface reactions that correspond to a general reaction network were computed with cluster DFT methods. The network included many reaction pathways from the dissociative chemisorption of methane up to adsorbed CO. The surface reactions included dehydrogenation reactions of adsorbed CH x species and oxidation of these species by adsorbed OH. It was found that the main reaction pathway is CH4 → *CH3 → *CH2 → *CH → *CHOH → *CHO → *CO, where * denotes an adsorbed species. Frequency analysis and transition-state theory were employed to show that the methane chemisorption elementary step, the first step in the above pathway, is rate-limiting. As a first approximation, electrolyte effects were not included in the model. In the second part of the work, the dissociative chemisorption of methane on the transition metal catalysts Ru, Rh, Pd, Os, Ir and Pt was studied using cluster DFT methods. The objective was to explore trends in the reactivity of these metals towards dissociating methane as well as the structure-sensitivity of the reaction. Different clusters were used to simulate close-packed, adatom and step sites. Reaction coordinate calculations were performed. It was found that for terrace sites the energy barrier was lowest for Ru, and was higher for metals with higher d-band occupancy. It was also found that for adatom and step sites, the energy barriers for the 5d metals Os, Ir, Pt were significantly lower than those for the 4d metals Ru, Rh, Pd. A Natural Bond Orbital analysis was performed to identify the reasons for the different reactivity of a Pt and a Ru ad-atom. In the third part of the work, the dissociation of water on the close-packed surfaces of Ru, Rh, Pd, Os, Ir, Pt and a Pt-Ru alloy, was studied using cluster DFT methods. Reaction coordinate calculations were performed and the results identified trends in the energy barriers and binding energies. The energy barrier for water dissociation was smaller for Ru and Os, and increased for metals with increased d-band occupancy. The binding energy of OH was lowest on Pt among all metals that were used. The weaker binding of OH on Pt suggests that OH is more reactive on Pt and occupies a smaller fraction of surface sites. This explains the experimentally observed higher reactivity of Pt in electrooxidizing methane, compared to other metals. On the other hand, by comparing the model predictions with steam-reforming experimental data, it was found that the trends in the reactivity of transition metals can be either determined by the energy barrier for methane dissociation or the binding energies of the dissociated water species.
Keywords: Engineering, Chemical.